Histological after arm tip amputation in the brittle star Ophioplocus januarii (Echinodermata: Ophiuroidea) - Di Giorgio, Gisele Vanesa (2015)
Echinodermata present a high regenerative potential expressed at different anatomical levels in bothadults and larvae. Wound healing in the arm tip after amputation in the brittle star Ophioplocus januarii wasexamined in San José gulf, Argentina, to observe histological and morphological changes. The process of woundhealing is described and compared with other brittle stars species. This process in O. januarii involves the closureof the wound, the repair of the tissue damage and posterior formation of a presumptive stalked blastema byundifferentiated cells, sclerocytes and presumptive blastemic cells. The sclerocytes are the more abundant celltype due to this cells are crucial to the future skeleton regeneration. The results found in this study supports theresuls found in others brittle stars